PEMERIKSAAN KADAR KOLESTEROL DARAH DAN KOMPOSISI LEMAK TUBUH PADA MASYARAKAT MENDALO INDAH DI KLINIK UNJA SMART SEBAGAI SKRINING AWAL HIPERKOLESTEROLEMIA - Syauqy, Ahmad; Puspasari, Anggelia; Fairuz, Fairuz; Dewi, Hasna; Utami, Erisca Ayu (Universitas Jambi, 2023)
ABSTRACTMost people are reluctant to be screened hypercholesterolemia. The cause of the reluctance diverse, ranging from the aspect of cost, accessibility to the site inspection, the limitations of the infrastructure as well as aspects of time. It is necessary for community service activities to facilitate this. Activities was held on November 2, 2022, in the form of checks blood pressure and cholesterol levels in the general population who are visiting the Jambi City Governor’s Field during a car free day on Sunday, where on this day, people of the city of Jambi crowded been to Park Jomlo to exercise. The number of people who participated in this examination is 99 people. The examination was conducted using a digital cholesterol checks easy Tauch and after that, participants can consult with a team of dedicated and also receive treatment if their blood pressure and cholesterol levels exceed normal limits. From the implementation of the activity, the results that have normal cholesterol levels are 38 people (38.4%) and abnormal 61 people (61.6%), for examination of body fat composition, which has a percentage of normal body fat 12 people (12%) and abnormal 87 people (88%). While those who have normal visceral fat are 55 people (56%) and the abnormal is 44 people (44%). From the high abnormalities of cholesterol and body fat compositions have been carried out so that it is expected that there is an increase in awareness and understanding of the importance of hypercholesterolemia screening in society.Keywords: cholesterol, hypercholesterolemia ABSTRAKSebagian besar masyarakat enggan untuk melakukan skrining hiperkolesterolemia. Penyebab keengganan tersebut beragam, mulai dari aspek biaya, keterjangkauan ke lokasi pemeriksaan, keterbatasan sarana prasarana maupun aspek waktu. Untuk itu perlu dilakukan kegiatan pengabdian masyarakat untuk memfasilitasi hal tersebut. Kegiatan ini dilaksanakan pada tanggal 2 November 2022 diklinik UNJA Smart Mendalo. Peserta kegiatan ini berjumlah 99 orang yang berasal dari pegawai dan dosen UNJA serta masyarakat yang tinggal disekitar klinik UNJA Smart. Adapun bentuk kegiatannya berupa pemeriksaan tekanan darah, kadar kolesterol, dan komposisi lemak tubuh, konsultasi gratis dengan dokter sekaligus edukasi kesehatan serta juga mendapat pengobatan jika tekanan darah dan kadar kolesterolnya melebihi batas normal. Kegiatan ini akan menggunakan alat cek kolesterol digital easy tauch dan BIA merek omron. Dari pelaksanaan kegiatan didapat hasil yang memiliki kadar kolesterol normal sebanyak 38 orang (38,4 %) dan abnormal 61 orang (61,6%), Untuk pemeriksaan komposisi lemak tubuh , yang memiliki persentase lemak tubuh normal 12 orang (12%) dan abnormal 87 orang (88%). Sedangkan yang memiliki lemak visceral normal sebanyak 55 orang (56%) dan yang abnormal 44 orang (44%). Dari tingginya abnormalitas kadar kolesterol dan komposisi lemak tubuh telah dilakukan edukasi sehingga diharapkan ada peningkatan kesadaran dan pemahaman terhadap pentingnya screening hiperkolesterolemia di masyarakat.Kata kunci: kadar kolesterol, hiperkolesterolemia